Delafossite CuMnO2 as an Efficient Bifunctional Oxygen and Hydrogen Evolution Reaction Electrocatalyst for Water Splitting. Issue 6 (1st January 2019) - Mao, Lingbo; Mohan, Swati; Mao, Yuanbing
Abstract : Delafossite CuMnO2 powder composed of earth-abundant elements was synthesized by a sol-gel process and thoroughly characterized by powder X-ray diffraction, SEM, XPS, FT-IR, and Raman spectroscopy. More importantly, their electrocatalytic performances for oxygen and hydrogen evolution reactions (OER and HER) have been fully investigated by cyclic voltammetry, electrochemical impedance spectroscopy, and linear sweep voltammetry with a rotating electrode in 1 M KOH electrolyte versus Ag/AgCl. Based on the measurements from these CuMnO2 -based working electrodes, the specific capacitance, total charge, most accessible charge, electrochemically active surface area, and roughness factor were calculated for the first time. Their stability was also studied for cost-effective and active electrode material. Furthermore, by comparing measurements at 1600 rpm and no rotation of the electrodes in alkaline media, the delafossite CuMnO2  synthesized in this work showed current densities of 12.3 mA/cm 2 at 1600 rpm and 11.9 mA/cm 2 at no rotation for OER and 6.9 mA/cm 2 and 6.3 mA/cm 2 for HER. Overall, our study demonstrated that delafossite CuMnO2 possesses effective bifunctional OER and HER activities.